EXPLORING THE DIFFERENT TYPES OF TRANSLATION: A COMPREHENSIVE OVERVIEW - Makhliyo Azimova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
In this article I will try to provide a deep analysis of the different types of translations and their features. Various approaches and methods will be examined by employing in diverse translation contexts, involving literary translation, technical and legal translation. Apart from that I will explore the unique difficulties and demands connecting to each type by highlighting the necessity of being culturally sensitive and linguistic accuracy and subject matters are also important. Through understanding cultural differences, and translators can deliver the meaning of the text accurately and effectively